Towards greenhouse cultivation of Artemisia annua: The application of LEDs in regulating plant growth and secondary metabolism - Zhang, Ningyi; Yang, Haohong; Han, Tianqi; Kim, Hyoung Seok; Marcelis, Leo F. M. (Frontiers in Plant Science, 2023)
Artemisinin is a sesquiterpene lactone produced in glandular trichomes of Artemisia annua, and is extensively used in the treatment of malaria. Growth and secondary metabolism of A. annua are strongly regulated by environmental conditions, causing unstable supply and quality of raw materials from field grown plants. This study aimed to bring A. annua into greenhouse cultivation and to increase artemisinin production by manipulating greenhouse light environment using LEDs. A. annua plants were grown in a greenhouse compartment for five weeks in vegetative stage with either supplemental photosynthetically active radiation (PAR) (blue, green, red or white) or supplemental radiation outside PAR wavelength (far-red, UV-B or both). The colour of supplemental PAR hardly affected plant morphology and biomass, except that supplemental green decreased plant biomass by 15% (both fresh and dry mass) compared to supplemental white. Supplemental far-red increased final plant height by 23% whereas it decreased leaf area, plant fresh and dry weight by 30%, 17% and 7%, respectively, compared to the treatment without supplemental radiation. Supplemental UV-B decreased plant leaf area and dry weight (both by 7%). Interestingly, supplemental green and UV-B increased leaf glandular trichome density by 11% and 9%, respectively. However, concentrations of artemisinin, arteannuin B, dihydroartemisinic acid and artemisinic acid only exhibited marginal differences between the light treatments. There were no interactive effects of far-red and UV-B on plant biomass, morphology, trichome density and secondary metabolite concentrations. Our results illustrate the potential of applying light treatments in greenhouse production of A. annua to increase trichome density in vegetative stage. However, the trade-off between light effects on plant growth and trichome initiation needs to be considered. Moreover, the underlying mechanisms of light spectrum regulation on artemisinin biosynthesis need further clarification to enhance artemisinin yield in greenhouse production of A. annua.